1991
DOI: 10.1128/jvi.65.9.5013-5028.1991
|View full text |Cite
|
Sign up to set email alerts
|

Infection by coronavirus JHM of rat neurons and oligodendrocyte-type-2 astrocyte lineage cells during distinct developmental stages

Abstract: Primary telencephalic cultures derived from neonatal Wistar Furth rats were able to support the growth of coronavirus JHM if a viable neuronal population was maintained. This occurred under serum-free defined, but not serum-supplemented, growth conditions. The importance of neurons in establishing infections in mixed cultures was confirmed by immunocytochemical and electron microscopic studies. Glia, although more abundant than neurons in these cultures, were less frequently infected during the initial 48 h po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 70 publications
5
16
0
Order By: Relevance
“…Studies from a number of disciplines are showing that cell-to-cell interactions playa role in the survival, proliferation, and differentiation of cell populations. These influences have also been shown to be critical in the establishment of JHM virus infections in primary rat telencephalic cultures (Pasick and Dales, 1991). The studies reported here support earlier observations indicating that cell-to-cell interactions can influence retinal and RPE cell survival and proliferation (Campochiaro and Glaser, 1968).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Studies from a number of disciplines are showing that cell-to-cell interactions playa role in the survival, proliferation, and differentiation of cell populations. These influences have also been shown to be critical in the establishment of JHM virus infections in primary rat telencephalic cultures (Pasick and Dales, 1991). The studies reported here support earlier observations indicating that cell-to-cell interactions can influence retinal and RPE cell survival and proliferation (Campochiaro and Glaser, 1968).…”
Section: Discussionsupporting
confidence: 88%
“…This virus replication may also reflect a need for cell-to-cell interactions and/or a requirement for more differentiated cell types. Recent studies by Pasick and Dales (1991) indicate that two cell types, neurons and early oligodendrocyte type 2 astrocyte lineage cells, and specific stages of differentiation may be necessary for productive JHM virus replication. They discovered that the presence of soluble mediators which synergistically block 0-2A cells from differentiating into oligodendrocytes was correlated with specific and reversible resistance to JHM virus infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This differential entry may reflect the presence of different receptors utilized by wild-type virus versus selected variants. In addition, the susceptibility of different neural cells to JHM is known to be affected by the developmental stages of different cell species and host factors (Pasick and Dales, 1991). In the case of infection by JHM mutants, the immune response clears virus from the white matter by 12 days postinoculation but has the deleterious consequence of inducing myelin loss (Wang eT al., 1990).…”
Section: Discussionmentioning
confidence: 99%